Simultaneous determination of dechloranes, polybrominated diphenyl ethers and novel brominated flame retardants in food and serum - Sales, Carlos; Poma, Giulia; Malarvannan, Govindan; Portolés, Tania; Beltrán, Joaquin; Covaci, Adrian (Analytical and bioanalytical chemistry, 2017)
A sensitive method for the simultaneous quantification of dechloranes, polybrominated diphenyl ethers (PBDEs) and novel brominated flame retardants (NBFRs) has been developed for gas chromatography (GC) coupled to tandem mass spectrometry operating in electron capture negative ionization (ECNI) mode. The major advance has been achieved by combining selected ion monitoring (SIM) and multiple reaction monitoring (MRM) modes in well-defined time windows, to determine dechloranes, PBDEs and NBFRs at picogram per gram level in one single analysis in complex matrix biological samples. From the chromatographic point of view, efforts were devoted to study several injection modes using multimode inlet (MMI) in order to obtain low instrumental detection limits, necessary for trace compounds such as Dechlorane Plus (DP) isomers. Method performance was also evaluated: calibration curves were linear from 20 fg μL −1 to 100 pg μL −1 for the studied compounds, with method detection limits at levels of 50 fg g −1 for DPs. Repeatability and reproducibility, expressed as relative standard deviation, were better than 5% even in solvent vent mode for the injection of standards. The application to a wide range of complex samples (including food, human and animal serum samples) indicated a sensitive and reliable way to quantify at the picogram per gram level 4 halogenated norbornenes (HNs), Dechlorane Plus ( anti -DP and syn -DP) and 2 of their homologues (Dechlorane-602 and Dechlorane-603), 11 PBDE congeners (no. 28, 47, 49, 66, 85, 99, 100, 153, 154, 183 and 209) and 5 novel BFRs, i.e. decabromodiphenyl ethane (DBDPE), 1,2-bis(2,4,6-tribromophenoxy)ethane (BTBPE), hexabromobenzene (HBB), 2,3,4,5-tetrabromo-ethylhexyl-benzoate (TBB) and tetrabromophthalate (TBPH). Graphical Abstract GC-ECNI-MS/MS chromatograms showing the most sensitive transition for DPs when injecting 2 μL of a 16 fg/μL standard solution of s-DP and a-DP at three different source temperatures